Experimental Demonstration for Enhancing Vocational Students’ Comprehension on Heat Transfer through Conduction and Radiation of Light Bulb - Nandiyanto, Asep Bayu Dani; Raziqi, Gulam Yasir; Dallyono, Ruswan; Sumardi, Kamin (Journal of Technical Education and Training, 2020)
This study aims to enhance the comprehension of vocational education students regarding heat transfer through conduction and radiation of light bulb using a conventional teaching supported by an experimental demonstration. The study was undertaken through several steps: (i) assessing students’ knowledge (by a pretest), (ii) delivering a teaching about heat transfer using a conventional teaching method, and (iii) experimental demonstration supported by a recorded video with explanatory materials. Each step was carefully evaluated by direct observation and evaluation (by assessing test). The evaluation was done by a pretest-posttest technique, supported by questionnaire survey and interviews for the qualitative analysis. The experimental demonstration was done by observing the heating phenomenon of a 5-Watt bulb lamp inside a cube with varied wall materials, and students observed the heat transfer phenomenon from the measurement of temperature as a function of time. During the teaching process, especially in the experimental demonstration, the students were asked strictly to focus and clearly observe what phenomenon was happening. The teaching analysis results showed that the students’ understanding improved significantly after the treatment using the experimental demonstration. The use of media also improved the students’ understanding, and instilled more information through the media by stimulating the students’ curiosity and interests in the subject. An analysis of the problems from the interviews and questionnaires was also conducted to reveal the main issues experienced because the delivered subject was not completely delivered in the curriculum. This study came up with new information on the need of additional experimental demonstrations and media (for repetition and clarification of the theoretical background for the happening phenomena) for improving students’ comprehension.